Memory and covenant the role of Israel's and God's memory in sustaining the deuteronomic and priestly covenants - Ellman, Barat (Minneapolis Fortress press, 2013)
Includes bibliographical references (p. 173-201) and indexes
creation-destruction-re-creation -- What is memory? -- Memory at work in the lived covenant. "Remember, do not forget": Israel's covenantal duty in Deuteronomy -- The priestly solution: sensory stimuli for God -- Israel's memory in the priestly tradition -- Memory and the transformation of priestly terms into lay concepts -- Signs for God -- Conclusion and comments
Dissertation unter dem Titel: Memory and religious praxis
Keywords: Bibel; Bund Gottes; Gedenken; Hochschulschrift